Technology Entrepreneurship Project (ENT 600) : Homebiogas / Muhammad Syafiq Nasaruddin - Nasaruddin, Muhammad Syafiq (2021)
Homebiogas company is a foreign company from Israel that focusing in producing methane gas by using bacteria that can be a source renewable energy that can replace usual cooking gas. In this company analysis, it is focusing on Homebiogas system that produce by this company to be identify, study and investigate along with problem they faced and what solution and action have been taken. The production of methane is based from biological concept. This gas is produced by bacteria in anaerobic condition. In this condition the bacteria will decompose food waste, animal waste and plant waste without present of oxygen. All of this waste will decompose by these bacteria in closing system. By this concept they need to create an efficient closing system in order to prevent bad odor and make sure their product is hygiene. Actually, this biogass already started been used at China and India in the 1970. Meanwhile in Malaysia this concept only been used by factory in order to produce their own electricity source. For example, at Jelutong there is company Sri Jelutong Biogas power plant. This power plant is using waste from palm oil to produce methane gas for combustion process in order to produce electricity for their own palm oil mill. So that, this renewable energy concept still didn’t been use for household in this country but have been started at other country. Based from that, by doing this case study we can analyze about the efficient biogas system that have been created by Homebiogas company that make them can bring their product into every house of their customer and what improvement that can made.